Non-clinical studies of the effectiveness of specialized sports nutrition product for correction of physical efficiency and psycho-physiological condition during intensive loads - T. Pushkina; E. Tokaev; T. Popova; A. Murashev; N. Tropskaya; E. Kislyakova; I. Shashkova; A. Zherebtsov (Спортивная медицина: наука и практика)
Objective: to study the impact of new specialized sports nutrition product with Siberian fir extract, superoxide dismutase, choline and oligomericproanthocyanidins on compensatory and adaptive capacities of the cardiovascular and respiratory systems, indicators of physical efficiency and psycho-physiological state in male rats during intense physical exertion. Materials and methods: experiments were performed on 40 male rats of the Wistar line. Control groups of animals received distilled water orally once a day every day for 21 days, experimental groups - the test product with dosage of 60 mg / kg. The experiments were performed in two stages. At the first stage the animals were subjected to exercise stress in form of a tail suspension, followed by jogging on a treadmill prior to failure on the 1st, 10th and 20th days of the experiment. Before and after the load, an electrocardiogram and a pneumogram were recorded. At the second stage the animals were subjected to swimming to failure with the subsequent measurement of grip strength on the 1st, 10th and 20th days of the experiment. On the 21st day of the experiment, after a swim test and measurement of the grip strength locomotor activity and navigational memory of the animals was evaluated. Results: animals receiving specialized nutrition had following features: a) after combined load included tail suspension and jogging on a treadmill a decrease of baseline values of breathing rate (BR) and heart rate (HR) and an increase of BR and HR after a physical load was observed by the 20th experimental day; B) the time of forced (limiting) swimming increased, and the locomotor activity and grip strength increased; C) a pronounced tendency to the time increment of entering the burrow was found, which indirectly indicated a decrease of the level of anxiety and an increase of the level of navigational memory. Conclusions: the effect of the tested specialized sports nutrition product was proved to enhance the compensatory abilities of the cardiovascular and respiratory systems, as well as for correction of indicators of physical efficiency and psycho-physiological state of male rats during intense physical exertion.